Analisis Rasio Aktivitas Operasi sebagai Alat Pengukur Kinerja Operasional: Studi Kasus pada PT Garudafood Tahun 2024 - Joni Hendra K; Riha Datul Aisyah; Santi Santi; Tira Reseki Pajriani (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
This study aims to analyze the operating activity ratio as a means of measuring operational performance at PT Garuda Food in 2024. Operational performance is an important indicator in assessing the effectiveness and efficiency of the company in carrying out its business activities. The activity ratios used in this study include Gross Profit Margin, Operating Profit Margin, Net Profit Margin, Cost To Sales Ratio, Operating Expenses To Sales Ratio, General Expenses To Sales Ratio and Selling Expenses To Sales Ratio. The method used is descriptive qualitative method with a case study approach, where the data analyzed comes from the financial statements of PT Garuda Food in 2024. The results showed that Gross Profit Margin, Operating Profit Margin, Net Profit Margin, Cost To Sales Ratio, Operating Expenses To Sales Ratio, General Expenses To Sales Ratio and Selling Expenses To Sales Ratio have increased compared to the previous year, which indicates improvements in operational efficiency. Meanwhile, the accounts receivable turnover ratio still shows a relatively low number, which indicates the need for increased effectiveness in managing business loans. Overall, the operating activity ratio can be used as an effective tool to rotate and improve the company's operational operations.